Riesgo de Diabetes Mellitus tipo 2 en personas con discapacidad que asisten al Ministerio de Inclusión Económica y Social Loja - Duarte Torres, Arianna Carolina (2023)
Type 2 diabetes is a chronic-degenerative, multifactorial disease, characterized by a state of chronic hyperglycemia with a high incidence in the world. The purpose of this research was to establish the risk of developing type 2 diabetes mellitus within ten years, determine the type and degree of disability according to sex and age and its correlation in people with disabilities who attend the Ministry of Economic and Social Inclusion Loja. A quantitative, cross-sectional study was established, with a sample of 46 people with disabilities, predominantly male in the age range of 20 to 39 years with 52.2% (n=24), in whom the disability card was reviewed and applied to the Findrisc Test. Obtaining that 63.04% (n=29) of the population presented low risk prevalence, while 21.74% (n=10) showed high risk prevalence, standing out in young female adults with 10.87% (n=5). Regarding the type of disability, 89.13% (n=41) correspond to intellectual disability, standing out men from 40 to 64 years with 50% (n=23); the degree of severe disability prevailed with 56.52% (n=26). When relating the variables type of disability and Findrisc risk with Chi Square of 1.942 and value of p=0.925, likewise, the relationship degree of disability and Findrisc risk with chi square of 7.045 and value of p=0.317, concluding that, no there is a statistically significant relationship between the variables prevalence of risk of Type 2 Diabetes Mellitus, type and degree of disability